Deleuze and the city - Frichot, Hélène 1970-; Gabrielsson, Catharina; Metzger, Jonathan 1978- (Deleuze connections, 2016)
Uses the philosophy of Deleuze and Guattari to interrogate what cities can doDefining the lives of a majority of the world's population, the question of 'the city' has risen to the fore as one the most urgent issues of our time - uniting concerns across the terrain of climate policies, global financing, localised struggles and multi-disciplinary research.Deleuze and the City rests on a conviction that philosophy is crucially important for advancing knowledge on cities, and for allowing us to envisage new forms of urban life toward a more sustainable future. It gathers some of the most original thinkers and accomplished scholars in contemporary urban studies, showing how Deleuze and Guattari's philosophical project is essential for our thinking through the multi-scalar, uneven and contested landscapes that constitute 'the city' today.